Peran Pendidikan Kepramukaan dalam Membangun Karakter di Kelas III MI Darunnajah 2 Cipining - Putri, Nadia Nurrosyda; Pratama, Arizqi Ihsan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
This article aims to examine the role of the scout movement in forming the character of social care and independence as the the expectations of government and society. Methods: This study used a qualitative approach, descriptive analytic by using the instrument observation, interviews, and documentation. Then continued with the analysis using method of Miles & Huberman. Results: Efforts to establish the character of the Scout Movement of SDIT Al-Ukhwah is understanding, sincerity, hard work, struggling earnestly, obedience, sacrifice, commitment, consistency, brotherhood and trust. The supporter basic principles of scouting, scouting methods, and code of honor.